Rapid analysis and identification of dianthrone glycosides in Polygoni Multiflori Caulis based on enrichment of macroporous absorbent resin and UPLC‐Q‐TOF‐MS/MS. Issue 6 (30th April 2021) - Bo, Rui; Wu, Jian; Wu, Jiacai; Bai, Lisha; Ye, Mingzhu; Huang, Li; Chen, Hongyuan; Rui, Wen
Abstract: Introduction: Polygoni Multiflori Caulis (PMC) has been used as a traditional Chinese medicine for a long time in China. However, hepatotoxic events of PMC have been reported in recent years, but the potential toxic compounds have remained unclear. Dianthrones as the secondary plant metabolites were revealed to potential hepatotoxicity in a previous study. However, no reports focused on dianthrones in PMC. Objective: In the quest for exploring potential hepatotoxic compounds in PMC, the aim of this work was to undertake a comprehensive characterisation of dianthrones in PMC. Methods: A simple and effective macroporous absorbent resin column chromatography method was established in this study to enrich the minor dianthrones from PMC extracts. Exploration and characterisation of dianthrones in PMC was conducted by an ultra‐high‐performance liquid chromatography‐quadrupole time‐of‐flight tandem mass spectrometry (UPLC‐QTOF‐MS/MS) method and information dependent acquisition (IDA) mode. The aglycones of dianthrone glycosides were further verified by acid hydrolysis method. Results: Seventy‐two dianthrone glycosides and their five aglycones were discovered and tentatively characterised in PMC for the first time, of which 29 dianthrones were identified as potential new compounds. Dianthrone glycosides could be classified into three types according to their aglycone structures, and their fragmentation pathway rules and diagnosed ions were also summarised comprehensively. Conclusion: This was the first comprehensive investigation on dianthrones in PMC. The result would help to fully understand the phytochemical constituents and toxic components in PMC, and highlight the need for further toxicological investigations of the dianthrones in PMC due to their potential hepatotoxicity correlation. Abstract : A macroporous absorbent resin enrichment method coupled with UPLC/Q‐TOF‐MS/MS was utilized to identify the minor dianthrones in Polygoni Multiflori Caulis . Seventy‐seven dianthrones were tentatively identified in Polygoni Multiflori Caulis for the first time, including 30 potential new compounds. The acid hydrolysis method was established for structural verification.